The Biochemical and Molecular Basis for the Divergent Patterns in the Biosynthesis of Terpenes and Phenylpropenes in the Peltate Glands of Three Cultivars of Basil - Iijima, Yoko (American Society of Plant Biologists, 2004)
Surface glandular trichomes distributed throughout the aerial parts of sweet basil (Ocimum basilicum) produce and store monoterpene, sesquiterpene, and phenylpropene volatiles. Three distinct basil chemotypes were used to examine the molecular mechanisms underlying the divergence in their monoterpene and sesquiterpene content. The relative levels of specific terpenes in the glandular trichomes of each cultivar were correlated with the levels of transcripts for eight genes encoding distinct terpene synthases. In a cultivar that produces mostly (R)-linalool, transcripts of (R)-linalool synthase (LIS) were the most abundant of these eight. In a cultivar that synthesizes mostly geraniol, transcripts of geraniol synthase were the most abundant, but the glands of this cultivar also contained a transcript of an (R)-LIS gene with a 1-base insertion that caused a frameshift mutation. A geraniol synthase-LIS hybrid gene was constructed and expressed in Escherichia coli, and the protein catalyzed the formation of both geraniol and (R)-linalool from geranyl diphosphate. The total amounts of terpenes were correlated with total levels of terpene synthase activities, and negatively correlated with levels of phenylpropanoids and phenylalanine ammonia lyase activity. The relative levels of geranyl diphosphate synthase and farnesyl diphosphate synthase activities did not correlate with the total amount of terpenes produced, but showed some correlation with the ratio of monoterpenes to sesquiterpenes.